Analisis ROA, ROE, dan BOPO untuk Memprediksi Pertumbuhan Laba PT Bank Tabungan Pensiunan Nasional Syariah - Suhendro, Dedi; Annam, Rahmad (Fakultas Ekonomi dan Bisnis Islam, 2022)
The purpose of this study is to determine how independent variables, namely Return On Asset (ROA), Return On Equity (ROE), and Operating Expenses Operating Income (BOPO), affect the dependent variable, namely profit growth, both partially and simultaneously. This quantitative study collected data from PT Bank Tabungan Pensiunan Nasional Syariah, which can be accessed at www.btpnyariah.co.id. Secondary data is used in this study. This study uses a purposive sampling method for sampling. For data analysis, this study uses multiple linear regression analysis with regression equations in SPSS. The results of the hypothesis indicate that the independent variable Return On Asset (ROA) partially does not affect Profit Growth and the independent variable Return On Equity (ROE) partially does not affect Profit Growth. Simultaneously, the independent variables Return On Asset (ROA), Return On Equity (ROE) and Operating Expenses Operating Income (BOPO) on Profit Growth.